FRACTIONAL RESERVE BANKING: SEBUAH REPRESENTASI EKONOMI SEMU (TINJAUAN EKONOMI ISLAM) - Ayief Fathurrahman (Jurnal La Raiba UII, 2012)
This article explained that fractional reserve banking is a system full of risks, even threatening the stability of the economy. Its implications led to many phenomena of the crisises, the most obvious example is the occurrence of the great depression in the 1930’s. Related to this, Islam considers that fractional reserve banking is a great dengarous system, so that it has been considered contrary to the principles and values which brought by Islam. Concretely Islamic Bank offers a better system with the system profit and loss sharing (PLS). Its implicationis has been very positive, the stability of the economy is relatively high and can stimulate the investment climate without the fragile aspects of liquidity, because the 100% reserve banking is a must.